Therapeutic effect of Anakinra in the relapsing chronic phase of febrile infection–related epilepsy syndrome. Issue 2 (27th March 2019) - Dilena, Robertino; Mauri, Eleonora; Aronica, Eleonora; Bernasconi, Pia; Bana, Cristina; Cappelletti, Cristina; Carrabba, Giorgio; Ferrero, Stefano; Giorda, Roberto; Guez, Sophie; Scalia Catenacci, Stefano; Triulzi, Fabio; et al.
Summary: Febrile infection–related epilepsy syndrome (FIRES) is a severe epileptic encephalopathy with presumed inflammatory origin and lacking effective treatments. Anakinra is the human recombinant interleukin 1 receptor antagonist clinically used in autoinflammatory or autoimmune conditions. We report a case of FIRES for which the spatial and temporal match between electroencephalography (EEG) and magnetic resonance imaging (MRI) focal alterations provides support for the detrimental synergic interplay between seizures and inflammation that may evolve to permanent focal lesions and progressive brain atrophy in weeks to months. Brain biopsy showed aspects of chronic neuroinflammation with scarce parenchymal lymphocytes. We report the novel evidence that anakinra reduces the relapse of highly recurrent refractory seizures at 1.5 years after FIRES onset. Our evidence, together with previously reported therapeutic effects of anakinra administered since the first days of disease onset, support the hypothesis that interleukin 1β and inflammation‐related factors play a crucial role in seizure recurrence in both the acute and chronic stages of the disease.